2015
DOI: 10.15252/msb.20145808
|View full text |Cite
|
Sign up to set email alerts
|

The functional interactome of PYHIN immune regulators reveals IFIX is a sensor of viral DNA

Abstract: The human PYHIN proteins, AIM2, IFI16, IFIX, and MNDA, are critical regulators of immune response, transcription, apoptosis, and cell cycle. However, their protein interactions and underlying mechanisms remain largely uncharacterized. Here, we provide the interaction network for all PYHIN proteins and define a function in sensing of viral DNA for the previously uncharacterized IFIX protein. By designing a cell-based inducible system and integrating microscopy, immunoaffinity capture, quantitative mass spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
127
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(137 citation statements)
references
References 122 publications
(207 reference statements)
9
127
1
Order By: Relevance
“…Originally, IFI16 was shown to bind to cytosolic viral DNA, physically engage STING, and induce IFN production in macrophage-like THP-1 cells (33)(34)(35). However, across non-immune cell types, IFI16 predominantly localizes to the nucleus (29,31,36,37). We defined a multi-partite nuclear localization signal on IFI16 and observed that its deletion triggers the localization of IFI16 exclusively to the cytoplasm (36).…”
Section: Emergence Of Nuclear Dna Sensingmentioning
confidence: 90%
See 4 more Smart Citations
“…Originally, IFI16 was shown to bind to cytosolic viral DNA, physically engage STING, and induce IFN production in macrophage-like THP-1 cells (33)(34)(35). However, across non-immune cell types, IFI16 predominantly localizes to the nucleus (29,31,36,37). We defined a multi-partite nuclear localization signal on IFI16 and observed that its deletion triggers the localization of IFI16 exclusively to the cytoplasm (36).…”
Section: Emergence Of Nuclear Dna Sensingmentioning
confidence: 90%
“…A member of the interferon-inducible human PYHIN protein family (28,29), IFI16 possesses two C-terminal HIN200 domains that bind to DNA in a sequence-independent manner (30) and an N-terminal pyrin (PY) domain that mediates intramolecular homotypic interactions and cooperative assembly of IFI16 oligomers (31,32) (Fig. 1, A and B).…”
Section: Emergence Of Nuclear Dna Sensingmentioning
confidence: 99%
See 3 more Smart Citations